Compelling student voice: dialogic practices of public confession. Issue 1 (2nd January 2020) - Lefstein, Adam; Pollak, Itay; Segal, Aliza
ABSTRACT: Encouraging and developing voice in the classroom is a key aim of dialogic pedagogy, but teachers' elicitation of student voices is not always experienced as empowering. This case study investigates a sixth grade literacy lesson discussion about responding to peer group social ostracism. The teacher pressed students to adopt and articulate a stance on this socially and morally charged issue, resulting in a series of student public confessions. Using linguistic ethnographic micro-analytic methods, we examine the realization of voice in these events. Though some confessions were student-initiated, their contents were firmly directed by the teacher and dominated by her voice. Students were compelled to take a stand, and to express improper thoughts or actions, in an appropriate voice, or be challenged and/or judged inadequate. This case study shows how attempts to empower voice can back-fire; we argue that dialogic pedagogy should include a right to remain silent.